BARRIERS AND DIFFICULTIES FOR CSR DEVELOPMENT IN KAZAKHSTAN - Mussabekova, Ainur; Turganova, Alua; Aldanova, Malika (Nazarbayev University, Graduate School of Public Policy, 2021)
Corporate Social Responsibility, or CSR, has been attracting significant interest as one of the key instruments for governments in maintaining the sustainability of local communities. The CSR approaches include not only the economic profitability of companies but also the societal and environmental aspects. The purpose of our master’s project is to investigate the barriers and difficulties for CSR development in Kazakhstan via testing two hypotheses, specifically whether (i) a better understanding of CSR and enhanced communication among stakeholders (Akimats, companies, local communities/NGOs) results in the improved realization of CSR and (ii) better planning and availability of CSR monitoring & feedback tools/mechanisms by local authorities or Akimats increases realization of more sustainable projects which address local community needs. The research has been done with a focus on the oil & gas industry, based on the case-study example of the North Caspian Operating Company in Atyrau Oblast. The research findings have demonstrated that: (i) varied perceptions of CSR by stakeholders lead to a disparate understanding of the CSR realization process; (ii) insufficient involvement of certain stakeholders leads to poor communication among parties; (iii) the absence of a clearly defined national framework for CSR implementation results in the weak realization of CSR projects; (iv) Akimat’s objectives are not clearly defined, which leads to lack of planning and contribution; (v) limited opportunity for company’s long term planning leads to projects that don’t address the needs of the local community; (vi) Akimat lacks the expertise and knowledge to support the realization of CSR project from the government’s side, which leads to its dependency on company’s decision-making and capacity during the CSR realization process; (vii) the absence of CSR monitoring and feedback processes from the local governments results in the realization of non-sustainable projects.
Keywords: Corporate social responsibility; CSR; NGO; Akimat; Sustainability; Perception; Oil & Gas; NCOC; Type of access: Open Access